Expression of vitamin D receptors in the superior cervical ganglia of rats. (4th July 2018) - Grobe, M; Kretzschmar, G; Vuica, A; Filipovic, N
Abstract: We investigated the role of vitamin D in the sympathetic nervous system including the distribution of vitamin D receptors (VDR), 1α-hydroxylase and 24-hydroxylase (CYP24) in neuronal subpopulations and satellite glia in the superior cervical ganglia (SCGs) of rats using immunohistochemistry. VDR immunoreactivity was observed in the cytoplasm and nucleus of nearly all neurons in the SCG. Intensity of VDR fluorescence was significantly greater in the cytoplasm of neuropeptide Y (NPY) negative somata compared to NPY positive neurons. Immunoreactivity for 1α-hydroxylase also was observed in the cytoplasm of all neurons of the SCG, but the intensity of fluorescence was less in the nuclei. To the contrary, the immunoreactivity for CYP24 was stronger in the nuclei, although it was present at lower intensity also in the cytoplasm of neurons. VDR and 1α-hydroxylase immunofluorescence was observed in many non-neuron cells, except satellite glial cells, which exhibited weak CYP24 immunofluorescence. Expression of VDRs and key metabolizing enzymes indicated the importance of vitamin D in the autonomic nervous system and the ability of sympathetic neurons to activate and deactivate vitamin D for its autocrine and paracrine roles.